Bracing of Pectus Carinatum in Children: Current Practices - Pavol Omanik; Sergio Bruno Sesia; Katarina Kozlikova; Veronika Schmidtova; Miroslava Funakova; Frank-Martin Haecker (MDPI AG, 2024)
Background: Although effective, compressive orthotic bracing (COB) in children with pectus carinatum is still not standardized. This study has aimed to analyze current practices amongst members of the Chest Wall International Group (CWIG). Methods: A web-based questionnaire was mailed to all CWIG members at 208 departments. It included 30 questions regarding diagnostic work-up, age for COB indication, type of COB used, daily wearing time, treatment duration, complications, and recurrence rate. Results: Members from 44 departments have responded (institutional response rate 21.2%). A total of 93% consider COB as the first-line treatment for PC. A conventional COB (CC) is used in 59%, and the dynamic compression system (FMF) in 41%. The overall compliance rate is >80%. A total of 67% of responders consider COB to be indicated in patients <10 years. The actual wearing time is significantly shorter than the physician-recommended time (p < 0.01). FMF patients experience a significantly faster response than CC patients (p < 0.01). No recurrence of PC has been noted in 34%; recurrence rates of 10-30% have been noted in 61%. Conclusions: COB is the first-line treatment for PC with a high compliance rate. During puberty, the recurrence rate is high. Treatment standardization and follow-up until the end of puberty are recommended to enhance COB effectiveness.